2023
DOI: 10.3934/matersci.2023003
|View full text |Cite
|
Sign up to set email alerts
|

Fe-TiO<sub>2</sub>/zeolite H-A photocatalyst for degradation of waste dye (methylene blue) under UV irradiation

Abstract: <abstract> <p>Industrial wastewater contains non-biodegradable dyes that are highly toxic to humans and aquatic life. As solution from photocatalytic degradation, TiO<sub>2</sub> is one of the effective photocatalysts for wastewater degradation, but it has low adsorption power. To overcome this deficiency, this study synthesized a new photocatalyst by Fe-TiO<sub>2</sub>/zeolite H-A. The photocatalyst was successfully synthesized by the impregnation method and was systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, it can be seen that all of the nanocomposite films show poor transmission between 200 and 380 nm, indicating that the nanocomposite films have a good UV shielding effect on the near-ultraviolet region. TiO 2 colloid hydrosol exhibits highly selective photocatalysis to MB, so MB can be photodegraded by UV light under its catalysis. Therefore, it is an interesting experiment to assess the UV shielding effect of the material according to the photodegradation principle of MB. The UV shielding simulation experiment based on the photodegradation principle of MB and the UV shielding mechanistic diagram of WPU–PDA nanocomposites are displayed in Figure a,b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it can be seen that all of the nanocomposite films show poor transmission between 200 and 380 nm, indicating that the nanocomposite films have a good UV shielding effect on the near-ultraviolet region. TiO 2 colloid hydrosol exhibits highly selective photocatalysis to MB, so MB can be photodegraded by UV light under its catalysis. Therefore, it is an interesting experiment to assess the UV shielding effect of the material according to the photodegradation principle of MB. The UV shielding simulation experiment based on the photodegradation principle of MB and the UV shielding mechanistic diagram of WPU–PDA nanocomposites are displayed in Figure a,b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that doping multivalent Mn into ZnO enhances photocatalytic activity by improving charge separation and inhibiting recombination (Lu et al, 2012). Researchers have also developed novel composite materials, such as Fe‐TiO 2 /zeolite H‐a and Fe (III) cluster‐modified Bi 12 O 17 Cl 12 , which exhibit enhanced photocatalytic degradation efficiency compared with pure TiO 2 (Cahyanti et al, 2023; Meng et al, 2020). And the introduction of Mn 2+ into BiOCl increases the specific surface area, broadens the light absorption range, and promotes the separation of photogenerated carriers (Cao et al, 2020).…”
Section: Review On Photocatalytic Degradation Of Water Pollutantsmentioning
confidence: 99%
“…Household wastewater has been recycled using various methods. One is using the photodegradation method, namely utilizing ultraviolet light for the photocatalyst activity to absorb photons and simultaneously carry out transformation reactions at the material interface [1,2].…”
Section: Introductionmentioning
confidence: 99%